Making Way in Corpus-based Interpreting Studies (New Frontiers in Translation Studies,, 2018)
This book presents a collection of state-of-the-art work in corpus-based interpreting studies, highlighting international research on the properties of interpreted speech, based on naturalistic interpreting data. Interpreting research has long been hampered by the lack of naturalistic data that would allow researchers to make empirically valid generalizations about interpreting. The researchers who present their work here have played a pioneering role in the compilation of interpreting data and in the exploitation of that data. The collection focuses on both of these aspects, including a detailed overview of interpreting corpora, a collective paper on the way forward in corpus compilation and several studies on interpreted speech in diverse language pairs and interpreter-mediated settings, based on existing corpora.